Analysis of Students’ Motivation in English Learning Difficulties of Sidikalang Methodist Private High School - Fitriani Silaban; Putri Halimah; Margaret Stevani (Journal on Education, 2023)
This research analyzed the difficulties in English learning of students at Sidikalang Methodist Private High School, Dairi regency. The focus of this research was to find out students’ difficulties in mastering English competence. This research used a classical and individual approach in collecting qualitative and quantitative data. The procedures used context, input, process, and product / CIPP - Evaluation Model for its benefits to improve teaching quality. The data were analyzed using the McDonough & McDonough Model, namely: (1) Exploration of both student learning processes and their results, (2) Analyzing the results of exploration through questionnaires and interviews with students, (3) Conducting peer-debriefing, namely interviews with other teachers related to the method, content of the syllabus, whether it was in accordance with the needs of students. The results showed that English learning was difficult for high school students because of: (1) Felt coerced, (2) Low mastery of basic concepts/intake, (3) Less of support from their environment, (4) Could not memorize information well, and (5) Had fewer opportunities to practice. In connection with these findings, it was suggested that English teachers and institutions should facilitate and provide high motivation for their students in English learning process.